Infestation of Portulaca oleracea (Portulacaceae) plants by Neotuerta platensis (Lepidoptera: Noctuidae) larvae in Brazil: evaluations for five consecutive years - Menezes,C. W. G. (2024)
Abstract The bioecology and infestation aspects of Neotuerta platensis Berg, 1882 (Lepidoptera: Noctuidae) on plants are poorly known. This insect fed on the leaves of common purslane, Portulaca oleracea L. (Portulacaceae) for two consecutive years, which triggered its study in the following five years in Januária, Minas Gerais State, Brazil. The objective of this work was to study the bioecology and infestation aspects of N. platensis on P. oleracea plants in the field and laboratory. The mean duration (± SD) of the egg, larva and pupa stages was 3.6 ± 0.89, 11.5 ± 2.81 and 10.7 ± 1.97 days, respectively. The mean numbers of egg masses and eggs per female (± SD) were 3.8 ± 1.16 and 891.6 ± 116.83, respectively. The percentage of infested plants was 59, 74, 0, 78 and 75% and the mean numbers of larvae per plant (± SD) ranged from 0.7 ± 0.45 to 1.6 ± 0.49 individuals, respectively from 2015 to 2019. Neotuerta platensis larvae infested P. oleracea plants in four out of five years evaluated.